Satellite-derived albedo improves long-term lake energy balance modeling in the central Qinghai-Xizang Plateau - Linan Guo; Wenbin Sun; Yanhong Wu; Jianting Ju; Peizheng Song (Journal of Oceanology and Limnology, 2026)

Construction of icariin-loaded bone powder/PLA composite scaffold and its effect on osteogenic differentiation of hADSCs - Weiting Guo; Xinyue Liu; Yingchao Liu; Jingjing Zhu; Langyu He; Yiran Tang; Yuen Yee Cheng; Xiangqin Li; Linan Li; Hongfei Wang; Kedong Song (Tissue and Cell, 2026)

Inequality in distribution of atmospheric particulate matters and their health exposure risk in Beijing-Tianjin-Hebei, China - Linan Guo; Yuehan Wang; Yi Yang; Yurong Zheng; Li Zhou; Wenbin Sun (Atmospheric Pollution Research, 2026)

Experimental aerodynamic investigation of a suction sail model - Xinru Du; Jingpu Chen; Linan Guo; Yanxia Wang; Shiliang Hu; Hanfeng Wang; Xiyang Liu (Ocean Engineering, 2026)

Naturally Occurring Epialleles and Their Roles in Response to Climate Change in Birch - Bowei Chen; Tianxu Zhang; Yile Guo; Lesheng Cao; Xu Zhang; Shahid Ali; Renyi Ma; Linan Xie; Jiang Wang; Gaurav Zinta; Shanwen Sun; Guifeng Liu; et al. (Molecular Ecology, 2025)
Epigenetics has been proposed to be an important mechanism that enables plant species to respond and adapt to environmental and climatic fluctuations and is sometimes entirely uncoupled from genetic variation. Nevertheless, the extent of this uncoupling and the contribution of epigenetics to plant responses to global climate change have not been well studied, particularly in forest trees. Here, we generated a high‐quality genome assembly for Betula platyphylla , a key pioneer species in temperate and boreal forest ecosystems, one of the most sensitive areas to global warming. Extensive multi‐omics sequencing of naturally white birch across the 48 provenances captured their full scope of temperate/boreal forests in Northeast China. Using a genome‐wide association study (GWAS), it was shown that over 55% of differentially methylated regions (DMRs) were spontaneous, independent of genetic factors. More than 30% of the spontaneous DMRs were significantly associated with gene expression, that is, potential epialleles, which are primarily involved in metabolism and responses to abiotic stresses; and 1819 of these epialleles were significantly associated with bio‐climatic variables (i.e., climatic epialleles, cEpialleles). Integrating these cEpialleles into a gradient modelling framework revealed that the natural populations of Asian white birch at high altitude/latitude might be most vulnerable to future climates. Our findings highlight the importance of integrating epigenomic and climatic data sets to forecast the adaptive capacity of a key forest species to rapid climate change.

Systematical accumulating and regulating evaluations of leaf functional metabolites in geographically isolated edible medicinal plants of Piper sarmentosum - Liu Ziting; Wu Xiaoqing; Wang Kemei; Bai Yachao; Guo Aimin; Linan Huang; Liao Bin; Zhang Jun (Journal of Plant Physiology, 2025)

Correlation of cyclosporine A blood concentration with kidney injury for pediatric patients after hematopoietic stem cell transplantation: a retrospective cohort study - Wei Shi; Xin Qiu; Liang Huang; Linan Zeng; Runxin Lu; Hailong Li; Kun Zou; Zhijun Jia; Guo Cheng; Qin Yu; Limei Zhao; Lingli Zhang (European Journal of Clinical Pharmacology, 2025)

Graphite-enhanced methanogenesis in coal measure shale anaerobic digestion: Implications for increasing gas yield and CO2 utilization - Qian Wang; Fubo Gao; Xianbo Su; Yi Jin; Weizhong Zhao; Hongyu Guo; Linan Su; Liangwei Xu; Xiaowei Shi; Laizhong Ding; Shiyao Yu (Chemical Engineering Journal, 2025)

Phototransformation and photoreactivity of MPs-DOM in aqueous environment: Key role of MPs structure decoded by optical and molecular signatures - Saisai Guo; Linan Liu; Lan Wang; Jingchun Tang (Journal of Hazardous Materials, 2024)

Climate‐related naturally occurring epimutation and their roles in plant adaptation in A. thaliana - Bowei Chen; Min Wang; Yile Guo; Zihui Zhang; Wei Zhou; Lesheng Cao; Tianxu Zhang; Shahid Ali; Linan Xie; Yuhua Li; Gaurav Zinta; Shanwen Sun; et al. (Molecular Ecology, 2024)
DNA methylation has been proposed to be an important mechanism that allows plants to respond to their environments sometimes entirely uncoupled from genetic variation. To understand the genetic basis, biological functions and climatic relationships of DNA methylation at a population scale in Arabidopsis thaliana , we performed a genome‐wide association analysis with high‐quality single nucleotide polymorphisms (SNPs), and found that ~56% on average, especially in the CHH sequence context (71%), of the differentially methylated regions (DMRs) are not tagged by SNPs. Among them, a total of 3235 DMRs are significantly associated with gene expressions and potentially heritable. 655 of the 3235 DMRs are associated with climatic variables, and we experimentally verified one of them, HEI10 (HUMAN ENHANCER OF CELL INVASION NO.10). Such epigenetic loci could be subjected to natural selection thereby affecting plant adaptation, and would be expected to be an indicator of accessions at risk. We therefore incorporated these climate‐related DMRs into a gradient forest model, and found that the natural A. thaliana accessions in Southern Europe that may be most at risk under future climate change. Our findings highlight the importance of integrating DNA methylation that is independent of genetic variations, and climatic data to predict plants' vulnerability to future climate change.

Enhanced reductive degradation of trichloroethylene by ball milled nitridation of bimetallic Ni-ZVI: Combination effect of electron transfer and catalytic hydrogenation - Yinghao Shi; Dong Wang; Jiaming Guo; Feilong Gao; Linan Liu; Jingchun Tang (Journal of Cleaner Production, 2024)

SENP3 mediates the activation of the Wnt/β-catenin signaling pathway to accelerate the growth and metastasis of oesophagal squamous cell carcinoma in mice - Pengzeng Wang; Linan Yang; Yin Guo; Shuliang Qi; Jia Liang; Guo Tian; Ziqiang Tian (Functional & Integrative Genomics, 2024)

The reference range of lamotrigine in the treatment of epilepsy in children: a systematic review - Jingjing Chen; Liang Huang; Linan Zeng; Zhimei Jiang; Meiping Xiong; Zhi-Jun Jia; Guo Cheng; Liyan Miao; Limei Zhao; Lingli Zhang (European Journal of Clinical Pharmacology, 2024)
Purpose This study intends to assess the reference range of lamotrigine concentration for treating childhood epilepsy. Methods PubMed, Ovid-Embase, The Cochrane Library, CNKI, WanFang data and VIP databases were searched from database inception to January 2022. RCT, cohort study, case–control study, cross-sectional study that estimated the reference range of lamotrigine for children epilepsy treatment were included. The data extracted included basic information, statistical methods, data type, and results of reference range. Descriptive analysis was performed for them. Results 8 studies were included and estimated the reference range, and all of them were calculated based on efficacy data and/or concentration data. Statistical methods including ROC curve, concentration-effect curve, mean ± standard deviation, 95% confidence interval and percentile interval were utilized. For lamotrigine monotherapy, the lower limits ranged from 2.06 mg/L to 3.99 mg/L, and the upper limits ranged from 8.43 mg/L to 9.08 mg/L, showing basic consistency. However, for lamotrigine concomitant with valproate, the lower limits ranged from 2.00 mg/L to 8.00 mg/L, and the upper limit was 11.50 mg/L, for lamotrigine concomitant with other antiepileptics, the lower limits ranged from 1.00 mg/L to 3.09 mg/L, and the upper limits varied from 5.90 mg/L to 16.24 mg/L, indicating inconsistency. Conclusion Several studies have estimated the reference range of lamotrigine for childhood epilepsy, while controversy exist and no studies have determined the upper limit of the range based on safety data. To establish the optimal reference range, further high-quality studies are necessary that consider both efficacy and safety data.

Incidence and risk factors of drug-induced kidney injury in children: a systematic review and meta-analysis - Miao Zhang; Bingchen Lang; Hailong Li; Liang Huang; Linan Zeng; Zhi-Jun Jia; Guo Cheng; Yu Zhu; Lingli Zhang (European Journal of Clinical Pharmacology, 2023)

A numerical study on desalination performance enhancement by bipolar ionic diode nanochannels - Tong Li; Ran Peng; Tingting Zhang; Chenjie Wang; Linan Guo; Yongxin Song; Junsheng Wang; Minyi Xu (Desalination, 2023)

An Underwater Triboelectric Biomechanical Energy Harvester to Power the Electronic Tag of Marine Life - Bo Liu; Taili Du; Xiaoyan Xu; Jianhua Liu; Peng Zhu; Linan Guo; Yuanzheng Li; Tianrun Wang; Yongjiu Zou; Hao Wang; Peng Xu; Peiting Sun; et al. (Journal of Marine Science and Engineering, 2023)
Implantable electronic tags are crucial for the conservation of marine biodiversity. However, the power supply associated with these tags remains a significant challenge. In this study, an underwater flexible triboelectric nanogenerator (UF-TENG) was proposed to harvest the biomechanical energy from the movements of marine life, ensuring a consistent power source for the implantable devices. The UF-TENG, which is watertight by the protection of a hydrophobic poly(tetrafluoroethylene) film, consists of high stretchable carbon black-silicone as electrode and silicone as a dielectric material. This innovative design enhances the UF-TENG’s adaptability and biocompatibility with marine organisms. The UF-TENG’s performance was rigorously assessed under various conditions. Experimental data highlight a peak output of 14 V, 0.43 μA and 38 nC, with a peak power of 2.9 μW from only one unit. Notably, its performance exhibited minimal degradation even after three weeks, showing its excellent robustness. Furthermore, the UF-TENG is promising in the self-powered sensing of the environmental parameter and the marine life movement. Finally, a continuous power supply of an underwater temperature is achieved by paralleling UF-TENGs. These findings indicate the broad potential of UF-TENG technology in powering implantable electronic tags.

The effects of metals and mixture exposure on lung function and the potential mediating effects of oxidative stress - Hao Zeng; Bohua Dong; Nan Wang; Wenzhe Xu; Linan Guo; Jiajia Liu; Bo Fang; Lei Zhang; Qian Wang; Wenqi Yang; Manman Wang (Environmental Geochemistry and Health, 2023)

Research on Low-Frequency Vibration Monitoring Sensor Based on a Cantilever-Beam-Structured Triboelectric Nanogenerator - Xiu Xiao; Qunyi Wang; Bohan Yao; Linan Guo; Chuanqing Zhu; Cong Zhao; Ling Liu; Minyi Xu (Journal of Marine Science and Engineering, 2023)
Vibration sensing is of great significance in offshore engineering monitoring and safety detection. This paper presented a low-frequency vibration sensor (LV-TENG) based on a cantilever-beam-structured triboelectric nanogenerator, which can perform high-precision vibration sensing while conducting vibration energy collection effectively. The LV-TENG was composed of two aluminum electrode layers, a spring steel sheet covered with polytetrafluoroethylene (PTFE) and a first-order vibration mode structured frame. Under the excitation of external vibration, the spring steel sheet undergoes first-order modal vibrations between the aluminum electrodes and generates a periodically fluctuating electrical signal in the external circuit. The vibration profile of the cantilever beam was first analyzed theoretically to provide guidance for structural design. On this basis, the influence of the main structural parameters, including the structure of the Al electrode, the thickness of the steel plate, and the electronegative materials, on the output performance of LV-TENG was experimentally investigated and the structure was optimized to enhance electrical output. The results showed that the LV-TENG can accurately sense structure vibration with a frequency of 0.1 Hz to 5.0 Hz and an amplitude of 2.0 mm to 10.0 mm. The measured output voltage followed a positive linear relationship with frequency and the fitted correlation coefficient reached 0.994. The demonstration experiment indicated that the LV-TENG is expected to provide a new avenue for low-frequency vibration monitoring and can be used for structural health monitoring analysis in marine engineering.

Exposure to barium and blood pressure in children and adolescents: results from the 2003–2018 National Health and Nutrition Examination Survey - Hao Zeng; Qiong Wang; Haotian Wang; Linan Guo; Bo Fang; Lei Zhang; Xuesheng Wang; Qian Wang; Wenqi Yang; Manman Wang (Environmental Science and Pollution Research, 2022)

Theory and Application of Pseudo-Reservoir Hydraulic Stimulation for Coalbed Methane Indirect Extraction in Horizontal Well: Part 1—Theory - Qian Wang; Xianbo Su; Linan Su; Hongyu Guo; Jinxing Song; Zengliang Zhu (Natural Resources Research, 2020)

Theory and Application of Pseudo-Reservoir Hydraulic Stimulation for Coalbed Methane Indirect Extraction in Horizontal Well: Part 2—Application - Qian Wang; Xianbo Su; Linan Su; Hongyu Guo; Jinxing Song; Zengliang Zhu (Natural Resources Research, 2020)

Biodegradation of avermectin by Bacteroidetes endosymbiont strain LYH - Zaixing Li; Cunyi Song; Jingliang Yang; Jianbo Guo; Linan Xing (World Journal of Microbiology and Biotechnology, 2008)